Unintended Consequences Following the 2014 American Academy of Pediatrics Policy Change for Palivizumab Prophylaxis among Infants Born at Less than 29 Weeks' Gestation - Goldstein, Mitchell; Krilov, Leonard R.; Fergie, Jaime; Brannman, Lance; Wade, Sally W.; Kong, Amanda M.; Ambrose, Christopher S. (American Journal of Perinatology, 2020)
Objective The aim of this study is to compare outpatient respiratory syncytial virus (RSV) immunoprophylaxis (IP) use and relative RSV hospitalization (RSVH) rates for infants <29 weeks' gestational age (wGA) versus term infants before and after the 2014 American Academy of Pediatrics (AAP) policy change.Study Design Infants were identified in the MarketScan Commercial and Multi-State Medicaid databases. Outpatient RSV IP receipt and relative <29 wGA/term hospitalization risks in 2012 to 2014 and 2014 to 2016 were assessed using rate ratios and a difference-in-difference model.Results Outpatient RSV IP receipt by infants <29 wGA and aged <3 months in the Commercial and Medicaid populations and those aged 3 to <6 months in the Medicaid population declined after 2014. Relative RSVH risks for infants <29 wGA were numerically greater after 2014, with infants aged <3 months and Medicaid infants experiencing the greatest increases. Difference-in-difference results indicated a significantly increased relative risk of RSVH for infants <29 wGA versus term (both cohorts aged 0 to <6 months) in the Medicaid-insured population (1.68, p = 0.0054). A nonsignificant increase of similar magnitude occurred in the commercially insured population (1.57, p = 0.2867).Conclusion The 2014 policy change was associated with a decrease in RSV IP use and an increase in RSVH risk among otherwise healthy infants <29 wGA.
Keywords: respiratory syncytial virus; immunoprophylaxis; hospitalization rates; palivizumab